PENGEMBANGAN SISTEM INFORMASI PROPERTI SEWA BERBASIS WEB: PENDEKATAN DBLC DAN PERSPEKTIF MANAJEMEN SISTEM INFORMASI - Jihan Zhafira Thamrin; Nurhafifah Matondang; Rifka Dwi Amalia (Universitas Alma Ata, 2025)
Rental properties particularly boarding houses, require fast, accurate, and structured information to manage tenants, rooms, and payments at scale. This study designs and develops a web-based Rental Property Information System for â€œGrogol Mansionâ€ using the Database Life Cycle (DBLC) method. Requirements were elicited via interviews and observation, then modeled with ERD and translated into a relational schema implemented in PHPâ€“MySQL. Core modules include public room catalog & availability, account registration and booking, payment recording, tenant complaints, and an admin dashboard with multi-role access. Black-box testing and user acceptance testing (UAT) confirmed that all critical flows ran without errors, data were consistently recorded, confirmations/notifications appeared as expected, and UI response times met the â‰¤3-second criterion under normal load. The system improved operational efficiency, data accuracy, and service transparency, while providing a digital promotion channel. From a Management Information Systems perspective, the solution strengthens decision-making through structured data, controlled access, and auditable reports.